Effect of Copper Nanopartical and Magnetized Salty Water in Chlorophylls and Carotenoids content of Tomato (Lycopersicon esculentum L .) - Noora I. H. Al-Shemmary1, Basheer A. H. Al-Alwani2. , Rihab E. Kadhim2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The results of study showed that Cu nanoparticale at concentration of 5 M caused decreasing in chl.a content of tomato leaves significantly and the treatment of river water with Cu nanopartical at 5 M caused the highest value of chl.a (0.494 mg/g) , Cu nanoparticles of all it concentration caused decreasing in chl.b content of tomato leaves significantly comparing with control also with treatment of magnetic distilled water at 2000 Gauss, the concentrations of almost treatments increased the content of chl.b significantly comparing with control ,the treatment of drainage water(7 mmohs/cm) with magnetic water of 2000 Gauss caused the highest value of chl.b ( 0.695 mg/g). Cu nanoparticale at concentration of 0.5 M with magnetized distilled water caused decreasing in carotenoids of tomato leaves significantly, drainage water (7 mmohs/cm) with Cu nanoparticle at (0.5 and 9 M) caused decreasing in carotenoid comparing with control. The highest value of Cu nanopartical (9M) with drainage water ( 7 mmohs/cm) caused enhancement in carotenoid content (0.157 mg/g) comparing with control and treatment of drainage water at 7 mmohs/cm alone. Cu nanoparticale at concentration of 5 M caused decreasing of total chlorophyll content of tomato leaves significantly .